Cardiac Optimal Point: Identifying high risk patients for an optimal approach. (11th May 2022) - Brito, J; Silva, P; Aguiar-Ricardo, I; Cunha, N; Pinto, R; Raposo, M; Gregorio, C; Sousa, P; Caldeira, E; Miguel, S; Abreu, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: In recent years it has been proposed the concept of cardiorespiratory optimal point (COP) to best characterize populations who underwent cardiac rehabilitation programmes (CRP). The COP is defined as the minimum ratio between ventilation and oxygen consumption (VE/VO2) obtained during the cardiopulmonary exercise test (CPET) and it has been suggested that COP values > 30 conveyed worse prognosis. Purpose: To validate OP as a predictor of events and its correlation with exercise activity and quality of life on the long term. Methods: Single center observational study of patients enrolled on CRP - from February 2018 to May 2019 – who did CPET as part of routine evaluation. COP was defined as the lowest point of VE/VO2 ratio. Clinical and laboratorial characteristics were obtained at admission and discharge of CRP. Exercise practice was accessed using IPAQ questionnaire and quality of life was assessed based on a validated inquire - Kansas City Cardiomyopathy Questionnaire (KCCQ-23) – both by phone interview. Results: A total of 78 patients (mean age 63.2 ±11.6, 84.6% male) were evaluated and followed for a mean follow-up of 2, 68±0, 53 years. Main aetiology was ischemic heart disease (86%), followed by dilated cardiomyopathy (5, 1%) and valvular heart disease (2, 6%). A COP value above 30 correlated with a worse global score in KCC-23 (r =0.283, p = 0.47), and in particular domains such as frequency and severity of symptoms (p = 0.046, r 0.335 and p=0.16, r= 0.4, respectively), quality of life (p=0.039, r= 0.293) and social limitation (p = 0.001, r=0.5). COP also correlated with VO2 peak in basal CPET (p<0.001, r= 0.450) and on follow-up CPET (p= 0.39, r= 0.303). COP failed to predict events or levels of exercise activity on the long term, as evaluated by the IPAQ score. However, COP>30 did seem to correlate with a higher mortality rate on the follow-up although such trend was not statistically significant (possibly due to short follow-up time and sample size). Conclusion: COP values > 30 identify patients with worse prognosis, predicting worse quality of life and higher mortality. Although it did not seem to be a good predictor of exercise adherence after CRP.